Copper‐Catalyzed Enantioselective Allylic Alkylation with a γ‐Butyrolactone‐Derived Silyl Ketene Acetal. (16th December 2019) - Jette, Carina I.; Tong, Z. Jaron; Hadt, Ryan G.; Stoltz, Brian M.
Abstract: Herein, we report a Cu‐catalyzed enantioselective allylic alkylation using a γ‐butyrolactone‐derived silyl ketene acetal. Critical to the development of this work was the identification of a novel mono‐picolinamide ligand with the appropriate steric and electronic properties to afford the desired products in high yield (up to 96 %) and high ee (up to 95 %). Aryl, aliphatic, and unsubstituted allylic chlorides bearing a broad range of functionality are well‐tolerated. Spectroscopic studies reveal that a Cu I species is likely the active catalyst, and DFT calculations suggest ligand sterics play an important role in determining Cu coordination and thus catalyst geometry. Abstract : Eine Cu‐katalysierte enantioselektive Allylalkylierung unter Verwendung eines von γ‐Butyrolacton abgeleiteten Silylketenacetals als Nukleophil wird beschrieben. Entscheidend für die Entwicklung dieser Reaktion war die Identifizierung eines neuartigen Monopicolinamid‐Liganden mit den passenden sterischen und elektronischen Eigenschaften, um die gewünschten Alkylierungsprodukte in hoher Ausbeute und hohem Enantiomerenüberschuss zu erhalten.